Psychological stress associated with prognostic uncertainties in recently diagnosed Parkinson’s disease patients: A qualitative study - Yasmin H. Aboelzahab; Azadeh Bojmehrani; Yomna Elsheikh Ahmed; Heather Boon; Connie Marras; Richard Foty (PLoS ONE, 2025)
Background Parkinson’s disease (PD) is a common neurodegenerative disorder that negatively impacts thousands of patients in Canada. The unexpected nature of PD is associated with a decline in mental health. The highest level of psychological stress occurs during the early years following the diagnosis. Objectives To understand the psychological stress associated with prognostic uncertainties in recently diagnosed PD patients, uncover the gaps in the current support systems, and recommend areas for improvement in the support services that aim to decrease the psychological stress associated with receiving the PD diagnosis. Methods An exploratory qualitative study was conducted using semi-structured interviews with 13 PD patients diagnosed for more than 6 months and less than 5 years. Participants were recruited from the Toronto Western Hospital Movement Disorders Clinic, Toronto, Ontario, Canada until saturation of key themes was reached. Results Five major themes were identified capturing the lived experiences of PD patients following diagnosis: 1) the circumstances of receiving the diagnosis and its psychological impact on PD patients, 2) the impact of intrapersonal factors on the PD journey, 3) the role of social relationships in PD patient’s life, 4) the interaction of PD patients with different elements of the healthcare system, and 5) support services available for recently diagnosed PD patients. Conclusions This study uncovers the psychological burden faced by PD patients due to prognostic uncertainties and insufficient support systems. It emphasizes the importance of a patient-centered approach for improving their quality of life and healthcare experiences through personalized support services.